Judd-Ofelt Parameters of Sm3+-doped Alkali Telluroborate Glasses - Tuyen, Vu Phi (VNU Journal of Science: Mathematics - Physics; Vol 32 No 1, 2016)
Abstract: Alkali borotellurite glass (ABTe) doped with concentration of 0.5 mol% Sm 3+ ions was prepared by melting method. The absorption, luminescence spectra and lifetime of ABTe:Sm 3+ have been measured at room temperature. The results were analyzed using Judd–Ofelt (JO) theory, that gives the Ω λ intensity parameters, transition probabilities ( A R ), calculated branching ratios ( β R ), measured branching ratios ( β mes ) and stimulated emission cross-sections ( σ λp ) for 4 G 5/2 → 6 H J H H J transitions.  Keywords : Alkali borotellurite glass, Judd-Ofelt theory.